Strategies in coping with the COVID-19 pandemic by nursing professionals: doing and learning - Silva, Valdenir Almeida da; Mota, Rosana Santos; Mendes, Andreia Santos; Barros, Angela de Souza; Souza, Jamile Moreira Machado de; Sant’ana Brito, Joselina (International Journal for Innovation Education and Research, 2022)
Objective: To describe strategies in coping with the COVID-19 pandemic adopted by nursing professionals. Method: Qualitative research conducted in a public teaching hospital in Salvador  –  Bahia, Brazil, between September and October 2020. A total of 17 nursing professionals who work in a reference unit for symptomatic respiratory patients were interviewed. Data were collected through semi-structured interviews and analyzed in the IRAMUTEQ software. The project was approved by a Research Ethics Committee. Results: nursing professionals developed strategies to cope with the pandemic to care for patients with COVID-19, their own family members, the team and themselves. For patients, the strategies adopted include greater concern for comfort, safety and improvements in the communication process. The distancing of family members has given rise to the need for the use of technological resources to favor approximation. A greater concern was identified with the protection of team members and with themselves, as they emphasized the correct use of personal protective equipment as a way to feel more protected and safe, including emotionally. Conclusion: The strategies developed by the professionals emerged from the practice to the extent that they were experiencing care to patients with COVID-19. These strategies aimed to adopt measures for self-protection, protection of their family members and team colleagues; and humanized patient care.